2022
DOI: 10.1186/s12978-022-01461-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with unintended pregnancies among sexually active undergraduates in mainland China

Abstract: Background Unintended pregnancies (UIP) among unmarried sexually active college students in mainland China have emerged as a major reproductive health issue with detrimental personal and socioeconomic consequences. This cross-sectional study aimed to determine the prevalence and factors associated with UIP among sexually active undergraduates in mainland China. Methods Between September 8, 2019 and January 17, 2020, a total of 48,660 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Study's results showed that married youth were more likely to experience unplanned pregnancies than their equivalents. This finding is in keeping with results of studies in other parts of Africa which showed that married women were more likely to experience unplanned pregnancies [42,2]. Although there are some studies with contradictory findings, according to Sarvestani et al married women in the African context face various barriers to accessing family planning resources including spousal rejection of contraceptives [25].…”
Section: Discussionsupporting
confidence: 82%
“…Study's results showed that married youth were more likely to experience unplanned pregnancies than their equivalents. This finding is in keeping with results of studies in other parts of Africa which showed that married women were more likely to experience unplanned pregnancies [42,2]. Although there are some studies with contradictory findings, according to Sarvestani et al married women in the African context face various barriers to accessing family planning resources including spousal rejection of contraceptives [25].…”
Section: Discussionsupporting
confidence: 82%
“…One potential explanation for this trend could be the influence of the marriage market, where an increasing number of men in China may be choosing younger partners due to a rising male-to-female ratio. Another contributing factor might be that unmarried adolescents are engaging in more sexual activity without using reliable contraception 21 22. The neglect of sexual and reproductive health among adolescents in China is evident, given the lack of comprehensive sex education in schools and the failure of healthcare providers to offer the necessary support and non-judgmental services to this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the number of people who have high-risk sexual behaviors such as multiple sexual partners is increasing and their age is getting younger in China (39). This underscores the fact that minors are also at high risk of HPV infection (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%